High levels of monocytic myeloid-derived suppressor cells are associated with favorable outcome in patients with pneumonia and sepsis with multi-organ failure - Irene T. Schrijver; Eleni Karakike; Charlotte Théroude; Pétra Baumgartner; Alexandre Harari; Evangelos J. Giamarellos-Bourboulis; Thierry Calandra; Thierry Roger (Intensive Care Medicine Experimental, 2022)
Abstract Background Myeloid-derived suppressor cells (MDSCs) are immature myeloid cells with immunosuppressive functions sub-classified into monocytic and polymorphonuclear MDSCs (M-MDSCs and PMN-MDSCs). Clinical studies reported increased levels of MDSCs that were associated with poor outcome in sepsis patients. Since sepsis patients exhibit signs of inflammation and immunosuppression, MDSCs may provide benefit by dampening deleterious inflammation in some patients. To test this hypothesis, we measured MDSCs in critically ill sepsis patients with pneumonia and multi-organ dysfunctions and a high likelihood of death. Methods This was a prospective multicenter observational cohort study performed in eight ICUs in Athens and Thessaloniki, Greece, enrolling critically ill patients with pneumonia and sepsis with multi-organ dysfunctions. A flow cytometry approach using blood collected at study inclusion in tubes containing lyophilized antibodies combined to unsupervised clustering was developed to quantify M-MDSCs and PMN-MDSCs. Results Forty-eight patients were included, of whom 34 died within 90 days. At study inclusion, M-MDSCs and PMN-MDSCs were increased in sepsis patients when compared to healthy subjects (3.07% vs 0.96% and 22% vs 2.1% of leukocytes, respectively; p < 10–4). Increased PMN-MDSCs were associated with secondary infections (p = 0.024) and new sepsis episodes (p = 0.036). M-MDSCs were more abundant in survivors than in patients who died within 28 days (p = 0.028). Stratification of patients according to M-MDSC levels revealed that high levels of M-MDSC were associated with reduced 90-day mortality (high vs low M-MDSCs: 47% vs 84% mortality, p = 0.003, hazard ratio [HR] = 3.2, 95% CI 1.4–7.2). Combining high M-MDSC levels with low Acute Physiology and Chronic Health Evaluation (APACHE) II score improved patient stratification (M-MDSCshigh/APACHE IIlow vs M-MDSCslow/APACHE IIlow: 20% vs 80% 90-day mortality, p = 0.0096, HR = 7.2, 95% CI 1.6–32). In multivariate analyses high M-MDSCs remained correlated with improved survival in patients with low APACHE II score (p = 0.05, HR = 5.26, 95% CI 1.0–27.8). Conclusion This is the first study to associate high levels of M-MDSCs with improved survival in sepsis patients.